Citalopram inhibits platelet function independently of SERT-mediated 5-HT transport - Harvey G. Roweth (Nature Portfolio, 2018)
Abstract Citalopram prevents serotonin (5-HT) uptake into platelets by blocking the serotonin reuptake transporter (SERT). Although some clinical data suggest that selective serotonin reuptake inhibitors (SSRIs) may affect haemostasis and thrombosis, these poorly-characterised effects are not well understood mechanistically and useful in vitro data is limited. We sought to determine whether the inhibitory effects of citalopram on platelets are mediated via its pharmacological inhibition of 5-HT transport. We quantified the inhibitory potency of (RS)-, (R)- and (S)-citalopram on platelet function. If SERT blockade is the primary mechanism for citalopram-mediated platelet inhibition, these potencies should show quantitative congruence with inhibition of 5-HT uptake. Our data show that citalopram inhibits platelet aggregation, adhesion and thromboxane production with no difference in potency between (R)- and (S)-isomers. By contrast, citalopram had a eudysmic ratio of approximately 17 (S > R) for SERT blockade. Furthermore, nanomolar concentrations of citalopram inhibited 5-HT uptake into platelets but had no effect on other platelet functions, which were inhibited by micromolar concentrations. Our data indicate that citalopram-induced inhibition of platelets in vitro is not mediated by blockade of 5-HT transport. This raises a new question for future investigation: by what mechanism(s) does citalopram inhibit platelets?